CLINICAL RELEVANCE OF HIGH SENSITIVITY C-REACTIVE PROTEIN IN ACUTE MYOCARDIAL INFARCTION PATIENTS - KAUR, KAMALDEEP; SINGH, DEEP INDER; AMITA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Poor cardiovascular outcomes have been linked to high-sensitivity C-reaction protein (hs-CRP), a biomarker of residual inflammatory risk. Whether or not a patient has diabetes mellitus, evaluate the relationship among hs-CRP levels estimated at hospital admission and in-hospital consequences and death. Methods: This prospective cohort study included 100 acute myocardial infarction (AMI) patients with both non-ST elevation myocardial infarction (STEMI) and STEMI who were admitted to the cardiac care critical care unit intensive therapy unit. Results: Diabetics had a considerably higher incidence of hypertension (p=0.001) and dyslipidemia (p=0.001) compared to non-diabetics. Diabetics exhibited a significantly higher mean hs-CRP level (6.76±1.12 vs. 3.65±0.98 mg/dL; p=0.01) than non-diabetics. Meanwhile, compared to non-diabetics, diabetics utilized significantly more aspirin (p=0.001), beta-blockers (p=0.001), angiotensin receptor blockers (ARBs) (p=0.01), and statins (p=0.001). Furthermore, compared to those with hs-CRP <3 mg/L, those with hs-CRP ≥3 mg/dL had a significantly higher incidence of dyslipidemia (p=0.001) and hypertension (p=0.001). Conclusion: The results of the current study demonstrated that hs-CRP upon admission is a valid predictor of hospital morbidity and death in patients with AMI who are diabetic or non-diabetic. Individuals with diabetes showed greater CRP levels than non-diabetic AMI patients did.